TECHNIQUE IN TEACHING READING TO THE SECOND YEAR STUDENT OF SMA MUHAMMADIYAH 1 SURAKART - RISHARYANI, RISHARYANI (2010)
his research aims at describing the implementation technique in teaching reading to the second year students of SMA Muhammadiyah 1 Surakarta. The data are taken from all elements of teaching reading process submitted by the teacher, the students and the other source such as; syllabus, lesson plan, etc. The data are collected by observation, documentation and interview and analyzed by using descriptive qualitative. The result shows that the techniques in teaching reading to the second year students of SMA Muhammadiyah 1 Surakarta are presentation of group discussion and question-answer. The problems faced by the teacher are; a) the teacher finds the difficulties in managing the students, b) the time is limited, c) the students have lack participation because the students are not attracted to the technique, d) the students have limited vocabulary that can cause the teaching reading does not run well, e) different ability among of the students. The problem solvings used by the teacher are; a) teacher walked around the class, give a point, and give a question to the students who do not pay attention, b) teacher must give extra time to change the time which is less, c) the teacher give song or watch a movie to the students, d) when the students can not receive the material in English language, the teacher translate into Indonesian, e) in the last session the teacher gives remediation. The writer concludes that the technique which is applied in teaching reading to the second year students of SMA Muhammadiyah 1 Surakarta has an important role in improving the reading competence. The students are more active and enjoy the lesson in the classroom.